2008
DOI: 10.1186/1750-1326-3-19
|View full text |Cite
|
Sign up to set email alerts
|

In vivo silencing of alpha-synuclein using naked siRNA

Abstract: Background: Overexpression of α-synuclein (SNCA) in families with multiplication mutations causes parkinsonism and subsequent dementia, characterized by diffuse Lewy Body disease postmortem. Genetic variability in SNCA contributes to risk of idiopathic Parkinson's disease (PD), possibly as a result of overexpression. SNCA downregulation is therefore a valid therapeutic target for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 30 publications
(26 reference statements)
1
100
0
1
Order By: Relevance
“…At the end of the 7-d infusion period, brains and CSF were collected for analysis. Consistent with previous studies demonstrating gene silencing in neuronal cells by intraparenchymal CNS siRNA infusion (Lewis et al 2008;Querbes et al 2009), a 33 ± 13% reduction in striatal Snca mRNA was measured in animals receiving the Snca siRNA compared with naïve animals. To analyze CSF RNA, pooled samples were subjected to high-speed centrifugation, and total RNA was isolated from the pellets.…”
Section: Resultssupporting
confidence: 89%
“…At the end of the 7-d infusion period, brains and CSF were collected for analysis. Consistent with previous studies demonstrating gene silencing in neuronal cells by intraparenchymal CNS siRNA infusion (Lewis et al 2008;Querbes et al 2009), a 33 ± 13% reduction in striatal Snca mRNA was measured in animals receiving the Snca siRNA compared with naïve animals. To analyze CSF RNA, pooled samples were subjected to high-speed centrifugation, and total RNA was isolated from the pellets.…”
Section: Resultssupporting
confidence: 89%
“…While progress will be made in this front, an alternative strategy is to deliver RNAi therapy by directly infusing synthetic siRNA into the CNS. Several groups have tested this strategy using different neurodegenerative disease models, including models for Huntington disease, Parkinson disease, and ALS (15,31,54). These experiments have shown that the infused siRNA can knockdown the expression of the target disease genes such as mutant huntingtin, a-synuclein, and SOD1, and in some cases, display modest therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…There are four previous reports of RNAi-mediated knockdown of endogenous α-synuclein in the adult CNS in vivo (63)(64)(65)(66). Naked siRNA infused into the mouse hippocampus gave rise to a significant 60%-80% reduction in Snca mRNA and a qualitative decrease in α-synuclein protein levels, but no overt cell loss or microgliosis (65). Naked siRNA infused into the primate midbrain caused a 50% reduction in SNCA mRNA, associated with a 40% reduction in α-synuclein.…”
Section: Aav-sh[snca] Rescues Function Deficits That Precede Degeneramentioning
confidence: 94%
“…However, acute knockdown of Snca in the adult brain could potentially cause unwanted effects by circumventing developmental compensatory mechanisms that occur in germline null mutants. There are four previous reports of RNAi-mediated knockdown of endogenous α-synuclein in the adult CNS in vivo (63)(64)(65)(66). Naked siRNA infused into the mouse hippocampus gave rise to a significant 60%-80% reduction in Snca mRNA and a qualitative decrease in α-synuclein protein levels, but no overt cell loss or microgliosis (65).…”
Section: Aav-sh[snca] Rescues Function Deficits That Precede Degeneramentioning
confidence: 96%